Use of Evidence-Based Management in Public Hospitals Management in Iran: A National Survey - Edris Hasanpoor; Ali Janati; Masumeh Gholizadeh; Elaheh Haghgoshayie (بیمارستان, 2018)
Background: Evidence-based Management (EBMgt) has been developed as a management model to improve the quality of management decisions. Hospital managers’ decisions can have a significant impact on service effectiveness and hospital success. Hence, this study aimed to survey sources of evidence among public hospitalschr('39') managers for decision-making in Iran.